BROLIGNAM: MEDIA UNTUK MENINGKATKAN PENGETAHUAN D2AN SIKAP TENTANG INDEKS GLIKEMIK SISWA SMA - Anita Kurniasari; Agus Wijanarka; Almira Sitasari (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
Background : The role of glycemic index on foods is very important especially in influencing diabetes mellitus because each kind of foods has specific glycemic index. Nowadays, teenagers can be susceptible to diabetes type 2 if they are not following healthy lifestyle. Research Objective : The purpose of this research is to investigate the effect on giving BROLIGNAM (brochure of nutrition education) about foods glycemic index towards knowledge and attitude among high school students. Method : This was quasi experimental design with pre test and post test with control group. T-test is used analyze data before and after media intervention and also the difference between control and intervention group. Result : There was significant difference of knowledge scores before and after media intervention (p=0,001) and there was significant difference attitude scores before and after media intervention (p=0,002). BROLIGNAM has significant effect on knowledge (p=0,001) but has no significant effect on attitude (p=0,877). Conclusion : The result suggest Brolignam may be a useful format to improve knowledge regarding to glycemic index among high school students